The potential impacts of nano-scale technologies on commodity markets : the implications for commodity dependent developing countries (South Centre GenevaCH, 2005)
Examines the potential impacts of nanotechnology on two sectors - agriculture and mining - in commodity dependent developing countries. Concludes with a number of specific policy recommendations to assist these countries confront the challenges and opportunites posed by rapidly emerging nano-scale science and technologies.
Bibliography: p. 55-58